2017
DOI: 10.15585/mmwr.ss6611a1
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Vaccination Coverage among Adult Populations — United States, 2015

Abstract: Problem/ConditionOverall, the prevalence of illness attributable to vaccine-preventable diseases is greater among adults than among children. Adults are recommended to receive vaccinations based on their age, underlying medical conditions, lifestyle, prior vaccinations, and other considerations. Updated vaccination recommendations from CDC are published annually in the U.S. Adult Immunization Schedule. Despite longstanding recommendations for use of many vaccines, vaccination coverage among U.S. adults is low.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
332
5
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(360 citation statements)
references
References 86 publications
(76 reference statements)
12
332
5
8
Order By: Relevance
“…An analysis of adult vaccination rates conducted in 2014 found that HBV vaccination rates remain low, among adults 19 years and older, only 25 percent were vaccinated. 24 Rates of HBV vaccination among people at high risk for infection, including men who have sex with men (MSM) and people who inject drugs (PWID), range from 25 to 44 percent. In 2014, among people newly infected with HBV for whom risk factor information was available, an estimated 20 percent of new HBV infections were among MSM and 26 percent were among PWID.…”
Section: The Risk For Developing Chronic Infection Is Related To Thementioning
confidence: 99%
“…An analysis of adult vaccination rates conducted in 2014 found that HBV vaccination rates remain low, among adults 19 years and older, only 25 percent were vaccinated. 24 Rates of HBV vaccination among people at high risk for infection, including men who have sex with men (MSM) and people who inject drugs (PWID), range from 25 to 44 percent. In 2014, among people newly infected with HBV for whom risk factor information was available, an estimated 20 percent of new HBV infections were among MSM and 26 percent were among PWID.…”
Section: The Risk For Developing Chronic Infection Is Related To Thementioning
confidence: 99%
“…Particularly, the prevalence of illness attributable to vaccine-preventable diseases is greater among adults than among children [2]. Yet, adult immunization coverage remains low for most routinely recommended vaccines and below targets even in countries such as the United States of America (USA) [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The recession post-intervention was not statistically significant. Total scores on the grading rubric were 11 (6) 61 (33) 79 (43) 34 (18) Reading materials on vaccine controversies provided in Practicum II.…”
Section: Discussionmentioning
confidence: 99%
“…5 Among adults, the rates of vaccinations are even more alarming with tetanus-diphtheria-acelluar pertussis (Tdap) and pneumococcal (high-risk populations) vaccination rates around 20% of populations that should be immunized. 6 These and other reports provide evidence of a growing number of patients who refuse to get themselves and their children vaccinated due to a belief that vaccines can cause harm.…”
Section: Introductionmentioning
confidence: 96%